2011
DOI: 10.1177/0148607111415109
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Protein and Energy Nutrition Decreases Mortality in Mechanically Ventilated, Critically Ill Patients

Abstract: Optimal nutritional therapy in mechanically ventilated, critically ill patients, defined as protein and energy targets reached, is associated with a decrease in 28-day mortality by 50%, whereas only reaching energy targets is not associated with a reduction in mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
217
1
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(243 citation statements)
references
References 32 publications
9
217
1
16
Order By: Relevance
“…Only an observational trial [14] and three RCTs in ICU patients have based the energy target on indirect calorimetry [12,15,16]: all four trials reported clinical benefits. Petros et al [16] prospectively tested hypocaloric (50 % of measured energy needs) versus isocaloric (100 % of measured energy needs) feeding in 100 patients with an indication for nutritional support during the first 7 days after ICU admission.…”
Section: Adapting Intakes To Measured Expenditure: a Key To Successmentioning
confidence: 99%
“…Only an observational trial [14] and three RCTs in ICU patients have based the energy target on indirect calorimetry [12,15,16]: all four trials reported clinical benefits. Petros et al [16] prospectively tested hypocaloric (50 % of measured energy needs) versus isocaloric (100 % of measured energy needs) feeding in 100 patients with an indication for nutritional support during the first 7 days after ICU admission.…”
Section: Adapting Intakes To Measured Expenditure: a Key To Successmentioning
confidence: 99%
“…An observational study showed that reaching clearly defined targets for energy and protein was associated with a decreased hazard ratio of death (18).…”
Section: Energy (Kcal) Requirementsmentioning
confidence: 99%
“…Большинство руководств рекомендуют приме-нение энтерального питания с высоким содержанием белка (от 1,2 до 2 г на кг идеальной массы тела в сутки) для больных, находящихся в критических состояниях. Применение ЭП с высоким содержанием белка было связано со снижением уровня смертности [7,[8][9][10]. В противоположность этому энтеральное питание с низ-ким содержанием белка не оказывает никакого влияния на смертность или количество инфекционных осложне-ний у больных в критическом состоянии, но может иметь некоторое значение у отдельных больных с почечной недостаточностью [11].…”
Section: составunclassified
“…В качестве примера в одном проспективном обсерва-ционном исследовании когорты из 886 больных, нахо-дившихся на ИВЛ, отмечено сокращение на 50% 28-днев-ной смертности у больных, достигших целевого уровня белка, по сравнению с пациентами, которые достигли целевых показателей только по калоражу [9]. Энтеральное питание с низким содержанием белка не рекомендуется в качестве рутинного энтерального питания у больных с острой или хронической почечной недостаточностью.…”
Section: составunclassified